Laser ablation of hepatocellular carcinoma-A review - Gough-Palmer, Antony Lawrence (The WJG Press and Baishideng, 2008)
A wide range of local thermal ablative therapies have been developed in the treatment of non resectable hepatocellular carcinoma (HCC) in the last decade. Laser ablation (LA) and radiofrequency ablation (RFA) are the two most widely used of these. This article provides an up to date overview of the role of laser ablation in the local treatment of HCC. General principles, technique, image guidance and patient selection are discussed. A review of published data on treatment efficacy, long term outcome and complication rates of laser ablation is included and comparison with RFA made. The role of laser ablation in combination with transcatheter arterial chemoembolization is also discussed.